2021
DOI: 10.1002/prp2.784
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol‐mediated RISK PI3K/AKT and MAPK/ERK pathways decreasing reperfusion myocardial damage

Abstract: Myocardial ischemia continues to be the first cause of morbimortality in the world; the definitive treatment is reperfusion; however, this action causes additional damage to ischemic myocardial tissue; this forces to seek therapies of cardioprotection to reduce this additional damage. There are many cardioprotective agents; within these, cannabinoids have shown to have beneficial effects, mainly cannabidiol (CBD). CBD is a non psychoactive cannabinoid. To evaluate the effect in experimental models of CBD in my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…CBD-mediated reduction of JNK activation has been shown in CBD-treated diabetic mice (1, 10, or 20 mg/kg) [ 85 ]. However, the study in Wistar rats indicated CBD (5 mg/kg)-induced PI3K/AKT and MAPK/ERK pathways associated with reducing reperfusion myocardial damage [ 86 ]. Moreover, CBD (4 μM) has been shown to reduce the p38 level in keratinocytes in the skin of healthy and psoriatic people [ 87 ].…”
Section: The Modulatory Activity Of Cannabidiol With Respect To the N...mentioning
confidence: 99%
“…CBD-mediated reduction of JNK activation has been shown in CBD-treated diabetic mice (1, 10, or 20 mg/kg) [ 85 ]. However, the study in Wistar rats indicated CBD (5 mg/kg)-induced PI3K/AKT and MAPK/ERK pathways associated with reducing reperfusion myocardial damage [ 86 ]. Moreover, CBD (4 μM) has been shown to reduce the p38 level in keratinocytes in the skin of healthy and psoriatic people [ 87 ].…”
Section: The Modulatory Activity Of Cannabidiol With Respect To the N...mentioning
confidence: 99%
“…Thus, acute application of CB 1 R antagonists reduced AT 1 R levels in rodent VSMCs [ 41 ] and human podocytes [ 63 ], and their chronic administration diminished the AT 1 R expression in the aorta of ApoE −/− mice [ 41 ], mouse heart [ 43 ], and kidney [ 63 , 64 ] isolated from diabetic mice and/or rats ( Table 2 ; Figure 4 ). A decrease in AT 1 Rs was also observed in response to chronic treatment of rats with cannabidiol (heart [ 44 ]) and PEA (kidney, arteries [ 44 , 51 ]).…”
Section: Resultsmentioning
confidence: 99%
“…The studies by Mattace Raso et al [ 50 , 51 ] and Franco-Vadillo et al [ 44 ] document a beneficial and CB 1 R-independent influence of two cannabinoids on the harmful effects of Ang II (for details, see Table 1 ). A decrease in AT 1 R densities was found in the heart [ 44 ], carotid and mesenteric arteries [ 51 ], and kidney [ 50 ] in response to chronic administration of CBD for 10 days to rats [ 44 ] or PEA for 5 weeks to hypertensive SHR and their normotensive WKY counterparts [ 50 , 51 ]. CBD or PEA treatment also reduced detrimental changes in cardiac [ 44 ], vascular and renal [ 50 , 51 ] tissues, and BP in SHR [ 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[20] This prevents the disruption of endothelial barrier function and inhibits atherosclerosis formation, [20] which is independent of cannabinoid receptor type 1 (CB1) and cannabinoid receptor type 2 (CB2) receptors. Moreover, CBD can exert a cardioprotective effect by relieving the infarcted myocardium in acute myocardial ischemia, [21][22][23][24] and ischemia reperfusioninduced ventricular arrhythmias through the activating of adenosine A1 receptors and the modulation of reperfusion injury salvage kinase (RISK)/phosphatidylinositol 3 kinases (PI3K)/protein kinase B (AKT) and mitogen-activated protein kinase (MAPK)/extracellular regulated protein kinases (ERK) pathways. [22,25] Diabetic cardiomyopathy is a unique prodrome that can lead to heart failure in diabetic patients, which is independent of the macrovascular complications of diabetes.…”
Section:  Cardiovascular Complicationsmentioning
confidence: 99%